THE STRATEGIC EXECUTION PLAN FOR ENHANCING FINANCIAL STRENGTH AND DIGITAL PERFORMANCE IN INDONESIA’S DIGITAL BANKING INDUSTRY - Syukron Sazly; Harun Al Rasyid; Agus Tri Indah K (Dynamic Management Journal, 2026)
This study aims to analyze the financial performance and digital performance of the five largest digital banks in Indonesia in 2025, and to formulate development strategies based on SWOT–TOWS analysis using a quantitative descriptive-analytical approach. The study integrates financial  indicators such as ROA, CAR, NPL and LDR , as well as digital performance; customer acquisition speed, innovation capability, ecosystem integration, and digital transaction growth. Data were obtained from  OJK , annual financial statements , and secondary industry sources. The results show,  digital banks demonstrate strong advantages in digital aspects, particularly in rapid user growth, service innovation, and integration with digital. All all banks maintain strong capital positions; however, profitability performance  relatively low. The SWOT–TOWS analysis indicates that strategies should emphasize ecosystem-based expansion (SO), improvement of profitability and service monetization (WO), strengthening competitiveness against conventional banks (ST), and risk management and sustainability (WT). Theresult, Indonesia’s digital banking industry is in a rapid growth phase but is not yet fully financially mature, requiring a balanced strategy between digital expansion and financial stability to achieve long-term sustainability.